Analyzing nanoparticle-induced neurotoxicity: A bibliometric analysis. (January 2020) - Wei, Xiaomin; Yang, Fuzhen; Chen, Defang; Li, Jun; Shi, Xiaohong; Li, Buran; Zhang, Chunling
Background: In recent years, nanoparticles have been widely used in many fields, ranging from cosmetics, agriculture, environment, and biomedical areas. The increasing use of nanoproducts induces a potential increasing exposure to human body, and then, unknown pathological consequences could increase. Methods: The database was searched from 2008 to 2018 by the Web of Science Core Collection. The bibliometric methods, CiteSpace and HistCite, were used for analysis and visualization of the data. Results: The 2932 publications were analyzed and the annual publications grew from 78 to 512 in a decade. The United States and China mainly contribute to this research area, which accounted for 29.5% and 22.9%, respectively. PLoS One, Scientific Reports, and Nanoscale were the three journals that published the most articles. Keyword analysis indicated that the major research direction was the mechanisms of nanoneurotoxicity, which included oxidative stress, inflammation, astrocyte activation, and the fibrillation of amyloid β protein. Conclusion: This bibliometric study revealed that nanoneurotoxicity was still a research hot topic and could be a promising area of research in the next few years. Nanoparticles play a role in neurodegenerative diseases by inducing reactive oxygen species production, inflammation, alterations of gene expression, and signal pathways.